ASUHAN KEPERAWATAN PADA KLIEN TN.H DENGAN GANGGUAN : Halusinasi Penglihatan Di Ruang Merak Rumah Sakit Jiwa Dr Soeharto Heerdjan Jakarta Barat - Timu Triadi (2020)
Abstract Hallucinations are a symptom of mental disorders for someone who has changed both from perception and sensory, there are several types of hallucinations including visual hallucinations where a person / individual loves to see shadows in the form of frightening objects, fun or in the form of invitations. The purpose of this study is to determine and apply nursing care to clients with vision hallucinations that include assessment, diagnosis, intervention, implementation and evaluation of nursing. This research method is descriptive by using a case study research method using 1 client with the problem of sensory perception of perception: hallucinations of vision in the Peacock Room of the Mental Hospital Dr. Soehrato Heerdjan, West Jakarta. Data collection techniques were narrated descriptively and carried out by interview techniques (client's identity, current or past history of illness, as well as experiences experienced by the client, physical examination and observation of client activities while in the treatment room). The results of the study the authors get from clients whose initials Tn. H with the problem of sensory perception disorder: hallucinations of vision as a core problem, the authors also get other diagnoses such as social isolation, low self-esteem, ineffective therapeutic regimens and risk of violent behavior. After holding 10 meetings, Mr. H can control hallucinations in several ways such as: rebuking, chatting with friends, doing activities and taking drugs according to a prescription from a doctor. Keywords: Nursing Care, Sensory Perception Disorders: Vision hallucinations